Central Neurocytoma: a Case Report (Pulse, 2014)
Central neurocytoma is a tumour showing neuronal differentiation. This tumour usually located in ventricles occurs at young age and carries favorable prognosis. For this, accurate diagnosis is essential. There is no published case report of central neurocytoma in Bangladesh. With these objectives, we have presented a case report of central neurocytoma in a 37 years old female. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20351 Pulse Vol.6 January-December 2013 p.51-52